2003
DOI: 10.1086/374372
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Large-Scale Structure in the X-Ray Sky

Abstract: We present the first results from a wide solid angle, moderately deep Chandra survey of the Lockman Hole North-West region. Our nine ACIS-I fields cover an effective solid angle of 0.4 deg 2 and reach a depth of 3 # ergs cm Ϫ2 s Ϫ1 in the 0.4-2 keV band and ergs cm Ϫ2 s Ϫ1 in the 2-8 keV band. The best-fit log N-Ϫ16 Ϫ15 10 3 # 10 log S for the entire field matches well onto that of the Chandra Deep Field-North. We show that the full range of the "cosmic variance" previously seen in different Chandra fields is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
86
5

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(105 citation statements)
references
References 30 publications
(42 reference statements)
14
86
5
Order By: Relevance
“…Puccetti et al (2006) are also in agreement with us (θ 0 = 12.8 ± 7.8 arcsec) within their large uncertainties. For a canonical slope of 0.8, Yang et al (2003) found θ 0 = 40±11 arcsec, much larger than ours (θ 0 = 5.9±0.3 arcsec) with a significance of ∼4σ. Such a strong clustering is somewhat surprising and it is much higher than any other reported angular clustering analysis in this band using a fixed canonical slope (although it is roughly consistent with the result of Basilakos et al 2004 for a fixed γ − 1 = 0.8).…”
Section: Resultscontrasting
confidence: 80%
See 2 more Smart Citations
“…Puccetti et al (2006) are also in agreement with us (θ 0 = 12.8 ± 7.8 arcsec) within their large uncertainties. For a canonical slope of 0.8, Yang et al (2003) found θ 0 = 40±11 arcsec, much larger than ours (θ 0 = 5.9±0.3 arcsec) with a significance of ∼4σ. Such a strong clustering is somewhat surprising and it is much higher than any other reported angular clustering analysis in this band using a fixed canonical slope (although it is roughly consistent with the result of Basilakos et al 2004 for a fixed γ − 1 = 0.8).…”
Section: Resultscontrasting
confidence: 80%
“…(2003) found a ∼2σ clustering signal in Chandra observations of the Lockman Hole North-West region with θ 0 = 4 ± 2 arcsec. The samples used by Yang et al (2003) and Miyaji et al (2007) reach limiting fluxes one order of magnitude deeper than that of our sample. Therefore, their very low correlation lengths compared with ours could be explained in terms of a dependence of the clustering strength on the flux limit of the sample involved (see Sect.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Solid line: reflection+leaky absorber model, see text for details. Cappelluti et al 2005Cappelluti et al , 2007Yang et al 2003, and references therein). These fluctuations have been explained by superposition of Poissonian noise and fluctuations introduced by the clustering of the sources.…”
Section: Discussionmentioning
confidence: 99%
“…However, the only current survey with a very high level of spectroscopic identifications is the Chandra Large Area Synoptic X-ray Survey (CLASXS), which consists of nine overlapped Chandra ACIS-I pointings in the Lockman Hole Northwest field covering ∼0.4 square degrees to X-ray flux limits of f 2−8 keV ≈3 × 10 −15 and f 0.5−2 keV ≈5 × 10 −16 ergs cm −2 s −1 . Yang et al (2003) found that the full range of cosmic variance seen in the earlier, individual Chandra pointings was represented in the number counts of the nine CLASXS pointings. They found the clustering in both the hard and soft X-ray bands to be significant, though, interestingly, the X-ray sources detected only in the hard band appeared to be substantially more clustered.…”
Section: Chandra X-ray Datamentioning
confidence: 89%